Polymorphism TaqIA Gen Dopamine D2 Receptor In Men Aged Start From 40 Years Old With Metabolic Syndrome Compared To Non Metabolic Syndrome - Syahputra, Muhammad Budi (Buletin Farmatera, 2019)
Introduction : Metabolic syndrome involves heritability , genetic , bad diet and lack of physical activity . One cause of the Metabolic Syndrome is a genetic abnormality in the dopamine D2 receptor gene that causes " Reward Deficiency Syndrome ".Aim: To investigate the relationship between polymorphisms of the dopamine D2 receptor gene Taq1A in men starting from 40 years of age with metabolic syndrome compared to those without metabolic syndrome.Methods: This research was done as an unpaired analytical research using case control design . The research subject is stored DNA isolates originating from metabolic syndrome 21 and 21 are non metabolic syndrome . Thermal Cycle process performed on isolates DNA using PCR techniques with applications located on a 310 bp band with a 2 % agarose gel , then the application in digestion with enzyme Taq1A ( New England Biolabs ®Inc ) and there are variant polymorphism ( T / C 310 bp , 180 bp , 130 bp ) , ( C / C 180 bp , 130 bp ) , ( T / T 310 bp ) and analyzed statistically using x² test , odds ratio.Result: Based on the metabolic syndrome X ² test was found genotype T / C at most ( 47.6 % ) , T / T ( 19.1 % ) , C / C ( 33.3 % ) with a value of p = 0.500 with a significance of p < 0 , 05 . In no metabolic syndrome T / C ( 61.9 % ) , T / T ( 9.5 % ) , C / C ( 28.6 % ) with a value of p = 0.457 with a significance of p < 0.05. Based on the distribution of allele no significant relationship.Conclusion: Based on the results of the study didn’t relate to the frequency distribution of genotype and allele distribution Taq1A polymorphisms of the dopamine D2 receptor gene in men aged from 40 years with the metabolic syndrome than those without metabolic syndrome